Analyzing Students’ Voice of Using Semantic Mapping Technique in Oral Presentation Class - Isry Laila Syathroh (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2020)
Oral presentation skill is one of the crucial skills which should be possessed by students in higher education. Students are expected to be able to express their ideas and show their understanding of the subject matter, either in verbal or non-verbal communication. Semantic mapping is a strategy which can be used to manage ideas in delivering topics of oral presentation. Therefore, the aim of this study is to explore what students perceive the use of semantic mapping in their oral presentation class. Thirty students were involved in this study. They joined 800 minutes of Teaching English to Young Learners (TEYL) subject. They should read and report what they have read orally through group presentations. Their oral presentation skills were assessed based on four aspects: quality of information and organization, quality of non-verbal communication, visual tools, appropriate use of terminology, as well as precision and details in the document produced. At the end of the course, it was revealed that the use of semantic mapping could help students in giving an effective oral presentation. It can improve students' performance in oral presentation project by enhancing the quality of presentation criteria aforementioned above. The result of the questionnaire also revealed that students positively perceive the use of semantic mapping when giving an oral presentation. They claim that the use of semantic mapping is beneficial for them for giving an effective oral presentation. Keywords: oral presentation, semantic mapping, students’ perception, TEYL